THE ROLE OF EPSTEIN-BARR VIRUS IN SYSTEMIC LUPUS ERYTHEMATOSUS - Miskovic, Rada; Banko, Ana; Raskovic, Sanvila (Medicinski podmladak, 2023)
Systemic lupus erythematosus (SLE) is a systemic autoimmune inflammatory disease that develops in a complex interaction of genetic and environmental factors. Viruses have long been recognized as important factors in the pathogenesis of lupus, especially the Epstein-Barr virus (EBV). A link between EBV and SLE has been suggested since the 1970s, and since then a growing body of evidence supports this link. In this mini-review, we have summarized the current knowledge on the role of EBV in SLE, focusing on the alterations in the immune response to EBV and the mechanisms of EBV-mediated autoimmunity induction in patients with SLE.